Bringing Islamic Leadership, Unity and Tolerance into Reality for the Stability of ASEAN Community - Nurliana Binti Mohd. Hassan (Institut Dirosat Islamiyah Al-Amien Prenduan, 2016)
This paper explains about a leader of a family or a country who not only holds power to communicate goals which create an inspiring vision while engaging people. It attempts to enlighten leadership throughmanaging the system by doing the right thing to promote a healthy norm highlighting a good leader as an end product of a good follower. But nowadays, the gen-Ys are causing worries to their elder ones. Therefore, to accommodate local contributions, it is suggested that leaders develop regular feedbacks at the same time improve leadership styles. Personal and professional changes create risk upon considering a successful plan though core beliefs in common practice is a combination of accepting unity and seeking room for tolerating individual differences. The complexity of responsibility truly depends on how a leader response towards an impactful scenario. The question is, what is causing social illness in the middle of Islamic Civilization? What are the qualities of a leader? Through a content analysis based research, the 5 element of Maqasid Syariah explores genuine guidelines toward understanding and recognizing religiosity while embracing and living with it leads a leader better. It tells about how a sustainable ummah relies solely on a knowledge-based society in order to enhance tolerance. Realistically, knowing alone is never enough. Upon that, this paper provides evidence that being mindful of other aspects of life reflects on the state of self actualization. Even then, gaining insights only blaze on facts rather than achievements. That rationalizes the reason and importance of being a creative and critical thinker as a Muslim leader. The implication of the findings are discussed through a list of agenda among the Muslim leaders that is to stabilize a culture of Taqwa in people’s behavior with the hope of creating a better place for ASEAN community.